Genetic and epigenetic catalysts in early-life programming of adult cardiometabolic disorders - Estampador AC (Dove Medical Press, 2014)
Angela C Estampador,1,2 Paul W Franks1,3,4 1Department of Clinical Sciences, Genetic and Molecular Epidemiology Unit, Lund University, Skåne University Hospital Malmö, Malmö, Sweden; 2Department of Endocrinology, Rigshospitalet, Copenhagen University Hospital, Copenhagen, Denmark; 3Department of Public Health and Clinical Medicine, Umeå University, Umeå, Sweden; 4Department of Nutrition, Harvard School of Public Health, Boston, MA, USA Abstract: Evidence has emerged across the past few decades that the lifetime risk of developing morbidities like type 2 diabetes, obesity, and cardiovascular disease may be influenced by exposures that occur in utero and in childhood. Developmental abnormalities are known to occur at various stages in fetal growth. Epidemiological and mechanistic studies have sought to delineate developmental processes and plausible risk factors influencing pregnancy outcomes and later health. Whether these observations reflect causal processes or are confounded by genetic and social factors remains unclear, although animal (and some human) studies suggest that epigenetic programming events may be involved. Regardless of the causal basis to observations of early-life risk factors and later disease risk, the fact that such associations exist and that they are of a fairly large magnitude justifies further research around this topic. Furthermore, additional information is needed to substantiate public health guidelines on lifestyle behaviors during pregnancy to improve infant health outcomes. Indeed, lifestyle intervention clinical trials in pregnancy are now coming online, where materials and data are being collected that should facilitate understanding of the causal nature of intrauterine exposures related with gestational weight gain, such as elevated maternal blood glucose concentrations. In this review, we provide an overview of these concepts. Keywords: early-life, epigenetic, programming, pregnancy, cardiometabolic, obesity, cardiovascular disease, type 2 diabetes